The return to work and how it is taxed: A dynamic perspective - Mike Brewer; Monica Costa Dias; Jonathan Shaw (Institute for Fiscal Studies (IFS), 2018)
This paper provides an empirical account of the dynamic return to work, and how this is affected by taxes and benefits. In doing so we bring the insights from the literature on dynamic labour supply to the issue of estimating the financial return to work and how it is taxed, where the past literature has focused on the current period return. We do this with two new summary measures: the forward-looking replacement rate (FLRR), which measures the dynamic return to working at all, and the forward-looking participation tax rate (FLPTR), which measures the impact of personal taxes and transfers on the dynamic return to work, and implement these using simulated data from a sophisticated, structural dynamic model of education and labour supply. We find that the dynamic return to work is much higher than a static measure would imply: at the start of working life, the expected FLRR and static RR differ by at least 5 percentage points for more than two thirds of women, and by over 10 percentage points for over a third of women. These results are driven by returns to experience. In contrast, we find a dynamic perspective makes relatively little difference to the extent to which personal taxes and transfers reduce the return to work, with the expected FLPTR and static PTR differing little for most women in our data. This mainly reflects the fact that that the UK tax and benefit system tends to treat the future returns to working today similarly to how it treats the current-period return.
Keywords: H21; H24; I38; J22; J24; 330; labour supply; work incentives; replacement rate; participation tax rate; forwardlooking; lifecycle; taxes; human capital